TEACHING METHODS FOR THE GRAMMAR OF THE RUSSIAN LANGUAGE ON THE EXAMPLE OF THE GRAMMATICAL CATEGORY - GENDER - Ismatullaev Abror Malikovich (Galaxy International Interdisciplinary Research Journal, 2021)
This paper discusses the role and significance of foreign languages. The author notes that proficiency in a second language is based on an understanding of the fact that grammar is a necessary basis for the full use of the Russian language both in scientific activity and in everyday life.